Detection of Sugars via Chirality Induced in Europium(III) Compounds - Wu, Tao; Průša, Jiří; Kessler, Jiří; Dračínský, Martin; Valenta, Jan; Bouř, Petr (Analytical chemistry, 2016)
Detection and resolution of simple monosaccharides are difficult tasks because their structure is quite similar. The present study shows that circularly polarized luminescence (CPL) induced in europium complexes provides very specific spectral patterns for fructose, mannose, glucose, and galactose. Differences were also observed between bare Eu(3+) ion and its complexes, when interacting with these sugars. The CPL spectra were measured on a Raman optical activity (ROA) spectrometer, which ensured high fluorescence intensity owing to the strong 532 nm laser excitation. The induced fluorescence was recorded in the same spectrum as the vibrational Raman bands. On the basis of the ligand field theory, most fluorescence spectral peaks could be assigned to f-shell europium transitions. Additional information on the interaction of the lanthanide with the sugar component was provided by measurement of time-dependent fluorescence, as formation of different complexes led to variations in fluorescence decay times. In nuclear magnetic resonance (NMR), the paramagnetic metal ion interacting with the sugars caused specific changes in (13)C chemical shifts. The spectroscopic data and molecular dynamics modeling showed that the interaction between the monosaccharides and Eu ion is rather weak due to the competition of the OH sugar groups with water molecules. However, multiple binding modes are possible, which contributes to the complexity and specificity of the spectra. The induced chirality and fluorescence spectra thus appear to be convenient means for monosaccharide detection and identification.
Keywords: Magnetic Resonance Spectroscopy; Luminescent Measurements; europium; magnetická rezonanční spektroskopie; Ramanova spektroskopie; luminiscenční měření; Luminescence; simulace molekulární dynamiky; Spectrum Analysis, Raman; Sugars; Europium; cukry; Molecular Dynamics Simulation; luminiscence